The Role of Technology in Modernizing Notary Services in the Era of Globalization - Syafriana, Rizka (Lembaga Riset Mutiara Akbar, 2024)
Currently it is the era of globalization, with the development of the digital era, the way people search for information has changed. With high intellectual ability and professionalism, it will allow democratization, openness, freedom of speech, free trade, and free competition. In the increasingly evolving digital era, information technology has changed the way people work, interact, and transact. The legal sector and legal agreements are also influenced by technology. The process of creating traditional legal documents, such as notary deeds, has changed with the advent of the concept of cyber notary. Especially in Indonesia, the spread of information technology to every aspect of people's lives is currently a problem. Because they are different from conventional agreements, electronic agreements can be carried out digitally even if the two parties do not meet in person, In order to obtain an adequate legal basis for the existence of a cyber notary, Indonesia needs to make changes to various regulations, namely the law on the position of a notary, Article 1868 of the Civil Code, and Article 5 paragraph (4) letter b of the Law on Information and Electronic Transactions to support the digitization of services best.